Gossypol exposure induces mitochondrial dysfunction and oxidative stress during mouse oocyte in vitro maturation. (1st October 2021) - Ding, Zhi-Ming; Chen, Yang-Wu; Wang, Yong-Sheng; Ahmad, Muhammad Jamil; Yang, Sheng-Ji; Duan, Ze-Qun; Liu, Ming; Yang, Cai-Xia; Xiong, Jia-Jun; Liang, Ai-Xin; Huo, Li-Jun
Abstract: Gossypol is a yellow natural polyphenolic compound extracted from the seeds, leaves, stems, and flower buds of the cotton plant. Several studies have shown that exposure to gossypol impacts reproductive health in both humans and animals. However, whether gossypol exposure would influence oocyte quality has not yet been determined. Here, we studied the effects of gossypol on the meiotic maturation of mouse oocytes in vitro . The results revealed that gossypol exposure did not affect germinal vesicle breakdown (GVBD) but significantly reduced polar body extrusion (PBE) rates. Moreover, we observed meiotic spindle organization and chromosome alignment were entirely disturbed after gossypol exposure. Further, gossypol exposure also caused mitochondrial dysfunction and abruptly decreased the levels of cellular ATP, and diminished the mitochondrial membrane potential (MMP). Accordingly, gossypol-induced oxidative stress was confirmed through an increased level of reactive oxygen species (ROS). Early apoptosis incidence also increased as identified by positive Annexin-V signaling. Collectively, the above findings provide evidence that gossypol exposure impaired oocyte meiotic maturation, disturbed spindle structure and chromosome dynamics, disrupted mitochondrial function, induced oxidative stress, and triggered early apoptosis. These findings emphasize gossypol's adverse effects on oocyte maturation and thus on female fertility. Highlights: Gossypol exposure compromised the meiotic maturation of mouse oocytes. Gossypol exposure disturbed the spindle assembly and chromosome alignment. Gossypol exposure caused mitochondrial damage and reduced ATP content and MMP. Gossypol exposure increased ROS level in mouse oocytes. Gossypol exposure induced early apoptosis in mouse oocytes.